The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0066-782x2004000600004
|View full text |Cite
|
Sign up to set email alerts
|

A ecocardiografia com contraste no diagnóstico de dilatações vasculares intrapulmonares em candidatos ao transplante hepático

Abstract: Contrast echocardiography proved to be effective, easy, and safe to use in candidates for liver transplantation. Transthoracic echocardiography may be used in the diagnostic routine of intrapulmonary vascular dilations, the transesophageal study being reserved for inconclusive cases with clinical suspicion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…(19) In the present study, the TTE results were suggestive of IPVD in 52% of the patients, which is in accordance with the results of other studies, in which rates ranging from 30 to 56% were reported. (4,(25)(26)(27) It is of note that, in the present study, the waiting time for transplantation was long (mean, 27 months). This is similar to that reported for other liver transplant centers before the MELD score came into use as a means of determining the position on the waiting list.…”
Section: Discussionmentioning
confidence: 55%
“…(19) In the present study, the TTE results were suggestive of IPVD in 52% of the patients, which is in accordance with the results of other studies, in which rates ranging from 30 to 56% were reported. (4,(25)(26)(27) It is of note that, in the present study, the waiting time for transplantation was long (mean, 27 months). This is similar to that reported for other liver transplant centers before the MELD score came into use as a means of determining the position on the waiting list.…”
Section: Discussionmentioning
confidence: 55%
“…While some authors stress the superiority of TEE, which avoids the false positives encountered in TTE, 70,71 one study has stressed the greater efficacy and sensitivity of TTE over TEE, suggesting that the latter should used only in cases of negative TTE. 72 However, these differences are probably due to differences in image quality, which is better when images are taken at the second harmonic frequency rather than at the fundamental frequency. 73,74 There is one report in which higher occurrence of IPVD in comparison to findings from other studies [72][73][74][75] was attributed to better resolution of the TTE images at the second harmonic.…”
Section: Diagnosing Of Ipvdmentioning
confidence: 99%
“…72 However, these differences are probably due to differences in image quality, which is better when images are taken at the second harmonic frequency rather than at the fundamental frequency. 73,74 There is one report in which higher occurrence of IPVD in comparison to findings from other studies [72][73][74][75] was attributed to better resolution of the TTE images at the second harmonic. 76 The sensitivity of TTE for diagnosing IPVD is currently questioned less than its capacity to rule out false-positive results, such as cases of patent foramen ovale.…”
Section: Diagnosing Of Ipvdmentioning
confidence: 99%
See 2 more Smart Citations